The biomechanical and functional relationships of the proximal radioulnar joint, distal radioulnar joint, and interosseous ligament. (June 2015) - Malone, P. S. C.; Cooley, J.; Morris, J.; Terenghi, G.; Lees, V. C.
This biomechanical study assessed integrated function of the proximal radioulnar joint (PRUJ), interosseous ligament (IOL), and distal radioulnar joint (DRUJ). Tekscan™ pressure sensors were inserted into the DRUJ and PRUJ of 15 cadaveric specimens. MicroStrain ® sensors were mounted onto the IOL on nine of these specimens. A customized biomechanical jig was used to apply axial loads and take measurements through pronosupination. The PRUJ, IOL, and DRUJ were shown to function as an integrated osseoligamentous system distributing applied load. The PRUJ has transmitted pressure profiles similar to those of the DRUJ. Different IOL components support loading at different stages of pronosupination. The IOL is lax during pronation. Mid-IOL tension peaks in the midrange of forearm rotation; distal-IOL tension peaks in supination. Axial loading consistently increases IOL strain in a non-linear fashion. There are clinical implications of this work: disease or surgical modification of any of these structures may compromise normal biomechanics and function.